Back Cover: Functionalization of Ruthenium(II)(η6‐p‐cymene)(3‐hydroxy‐2‐pyridone) Complexes with (Thio)Morpholine: Synthesis and Bioanalytical Studies (ChemPlusChem 6/2017). Issue 6 (13th April 2017) - Hanif, Muhammad; Meier, Samuel M.; Adhireksan, Zenita; Henke, Helena; Martic, Sanela; Movassaghi, Sanam; Labib, Mahmoud; Kandioller, Wolfgang; Jamieson, Stephen M. F.; Hejl, Michaela; Jakupec, Michael A.; Kraatz, Heinz‐Bernhard; et al.
Abstract : The cover picture shows the crystal structure formed from a {Ru II (η 6 ‐ p ‐cymene)} complex featuring a thiomorpholine substituent and the nucleosome core particle. The photograph featured as the background was taken on the North Island of New Zealand and shows the 'Champagne Pool' within the Waiotapu geothermal area, with the orange color coming from deposits of arsenic and antimony sulfides. Details are given in the Full Paper by C. G. Hartinger and co‐workers onpage 841 in Issue 6, 2017 (DOI:10.1002/cplu.201700050 ).